A dynamic mechanical stimulated and thermal-healed infrared modulator based on elastomer matrix with metal layer inspired by squid skin. (June 2022) - Song, S.; Xu, G.; Wang, B.; Liu, D.; Ren, Z.; Gu, J.; Wei, H.; Zhang, L.; Zhao, J.; Li, Y.
Abstract: Effective infrared (IR) modulation is crucial for engineered technologies, such as energy-efficient buildings, personal thermal management, multiple electronic instruments, adaptive thermal camouflage and smart thermoregulation. The static control occupies most portion in the past, to explore the materials that could dynamically modulate IR irradiation has emerged as an urgent scientific challenge. Drawing inspiration from squid skin, a dynamic IR modulator (Au-SEBS membrane) consisting of IR-reflective metal layer and IR-transparent elastomer matrix has been developed. Under a simple mechanical strain, the IR optical performance of Au-SEBS membrane including reflectance, transmittance, and absorptance alters, which is attributed to the generating microcracks at the metal layer. The results demonstrate that the reflectance varies from 97% to 37%, whereas 3%–51% for transmittance and 0%–12% for absorptance at the wavelength range of 2.5–25 μm. Additionally, the Au-SEBS membrane exhibits a distinctive thermal-healed ability due to the thermoplastic elastomer characteristic of SEBS copolymer. The material features a simple actuation mechanism, straightforward manipulate, fast response, and robust mechanical properties, which exhibits a promising potential for adaptive thermal camouflage, thermal management, and other related technologies that regulate the IR irradiation. Highlights: An infrared modulator was fabricated by stretchable infrared-transparent polymer matrix with infrared-reflective metal layer. The infrared reflectance and transmittance could be dynamicall2y modulated on-demand by an applied mechanical stimulus. The prepared modulator demonstrates a distinctive thermal-healed ability.